PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMP NEGERI DALAM WILAYAH KECAMATAN PEUSANGAN SIBLAH KRUENG KABUPATEN BIREUEN - Aidar, Aidar (JURNAL KEBANGSAAN, 2022)
This research was conducted on teachers of SMP Negeri Peusangan Siblah Krueng, Bireuen Regency by taking a sample of 69 teachers. The purpose of this study was to analyze a) the influence of the principal's leadership style on teacher performance, b) the effect of communication created in schools on teacher performance, c) the effect of teacher job satisfaction on teacher performance and d) the simultaneous influence of the principal's leadership style, communication and job satisfaction on teacher performance. The analytical method used is through statistical analysis and path models, because there is a causal relationship between the independent variables. The results of the study found that. 1) there is a positive influence of the principal's leadership style factor on teacher performance by 23.88%, 2) there is a significant influence of communication factors on teacher performance by 16.76%, 3) teacher job satisfaction affects teacher performance 10.30%, and 4) Simultaneously prove that the principal's leadership style, communication and job satisfaction have a significant effect on teacher performance, with the contribution of these three factors amounting to 53.5%. While the rest due to the role of variables that are not examined by 49.1%. These factors include school culture, compensation, teacher competence, education and training, and others.